Minutes
001-0023-001 PRIVATE & CONFIDENTIAL STANDING JOINT COMMITTEE OF INDUSTRIAL WOMEN'S ORGANISATIONS. MINUTES OF MEETING OF THE SPANISH RELIEF COMMITTEE, held on THURSDAY, 29th, October, 1936, at Transport House, Smith Square, London, S.W.1. at 2.30 p.m. PRESENT: Mrs. Leighton (in the chair); Mrs. Davey, Miss Elliott, Mrs. L'Estrange Malone, Miss Manicom, Mrs. Shepherd and Miss Sutherland (Secretary). APOLOGIES FOR ABSENCE. Apologies for absence were received from Mrs. Barton, Miss Colman, Mrs. Greenwood, Mrs. Martin and Mrs. Middleton. SUPPLY OF GARMENTS . The Secretary reported that she was waiting further information from the International Solidarity Fund as to garments required so that the previous list could be added to if necessary. SUPPLY OF WOOL. The Secretary reported that she had already received a number of knitted goods and supplies of wool, which she is distributing to Women's Sections and individuals who are willing to knit but cannot supply the wool themselves. It was agreed to purchase wool with the money received, and it was left to the Secretary to obtain samples and prices. It was further AGREED that representatives on the Standing Joint Committee be approached with a view to obtaining names of persons who would be willing to knit if wool were provided. OTHER APPEALS FOR HELP. The Secretary read the reply she has received from the Women's Co-operative Guild. It was AGREED that she should again approach Mrs. Barton, with a view to securing their co-operation. It was also AGREED that the affiliated Trade Unions be asked if they would be willing to circulate the Committee's appeal to their Branches, and to give the matter publicity in their respective journals. PRESS. The Secretary submitted a draft letter which she proposed sending to the Press. This was considered and endorsed and it was AGREED that it should be followed up with a further appeal. WORKING COMMITTEE. Names were suggested of members who would be willing to render assistance in the work of the Committee, when the Secretary desired it. DATE OF NEXT MEETING. It was AGREED that the date of the next meeting be left to the Secretary to arrange whenever necessary. THIS CONCLUDED THE BUSINESS. 292/946/1/23